CONCEPTUAL METAPHORS IN JUSTIN BIEBER'S SONG HOLY - Selvia; Heriyati, Nungki (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The purpose of this study is to reveal the use of conceptual metaphors in Justin Bieber's songs in the lyrics of his songs by focusing on identifying the domain and target domain of the metaphors used to find out the hidden or implied meaning in the song. This research method uses a qualitative descriptive method to describe and analyze the data that has been obtained from each Bieber song studied. The results of this study show that the characteristics, types of metaphors, and love schemes compared to each other in one sentence can produce diverse interpretations. In this study, the lyrics of Bieber's song 'Holy' use a lot of abstract metaphor characteristics, the type of metaphor uses a lot of orientation, and imagines a lot of space (contact) and force. So that knowing the meaning to be conveyed and the hidden intentions of the song can be understood.